P-P04 The cost of acute pancreatitis is amylasing!. (16th December 2021) - Carr, Harry; Morris, Timothy; Williams, Matthew; Jacob, Georgina; Courtney, Michael; Kanakala, Venkatesh
Abstract: Background: Amylase is the key serum biomarker in the diagnosis of acute pancreatitis, however there is no indication for repeat/serial measurement once the diagnosis is established. It is estimated that £27, 000pa is spent unnecessarily on repeat amylase investigations without clinical indication 1 . Anecdotally, within the department, unnecessary repeats were being routinely performed. Resultantly, we audited in 2019 and 2020 to understand the extent of the issue. Following the first cycle, pre-rotation departmental talks were given to all relevant healthcare staff. Aim(s): Determine and understand the extent of repeat amylase investigations and promoting factors. Assess the use of imaging. Methods: Data was collected and analysed retrospectively over 2 audit cycles (C1 & C2) from 79 patient episodes of admissions to the surgical department of a Northern Major Trauma Centre with confirmed diagnoses of acute pancreatitis between 01/05/2019 – 31/07/2019 and 01/08/2020 – 31/12/2020. Resources used included: patient notes, IMPAX and WebICE. Data was collected and analysed by one author in C1 but multiple authors in C2. Results: Mean age = 60 years. Male:Female ratio was 8:16 and 24:31, respectively. Initial amylase was diagnostic in > 75% (61/79). 81 unnecessary repeats performed. Most patients underwent imaging (75% and 67%) however, only approximately one-third (30.8% and 32.4%) of scans were performed to confirm the diagnosis. Despite imaging confirming the diagnosis in 88%, >50% of imaged patients had repeat amylase testing. Conclusions: The results demonstrate that our intervention, a pre-rotation departmental talk, has significantly reduced the over-requesting of amylase and current practice is of a good standard. Improvements are still required. Resultantly, we are additionally producing an electronic 'alert' into our investigations software that, on requesting a repeat amylase, will prompt clinicians to consider its necessity. Other centres offering acute treatment for similar patients may benefit from performing a similar audit to optimise care while reducing overall clinical costs.